Mechanism of chemical activation of expression of the endogenous ecotropic murine leukemia provirus Emv-3. - Mercer, J A (1990)
DBA/2 mice carry a single endogenous ecotropic murine leukemia provirus, Emv-3. This provirus is defective; it is very poorly expressed in young DBA/2 mice. The defect in Emv-3 is caused by a single base substitution in codon 3 of p15gag. The resulting amino acid substitution inhibits myristylation of the gag precursor and subsequent virus assembly. Despite this defect, percutaneous treatment of DBA/2 mice with the carcinogen and mutagen 7,12-dimethylbenz[a]anthracene (DMBA) induces ecotropic murine leukemia virus replication in virtually all treated mice. We hypothesized that this induction is the result of a DMBA-induced reverse mutation in codon 3 of p15gag which allows for efficient myristylation. We tested this hypothesis by isolating ecotropic viruses from DMBA-treated mice and determining the DNA sequences of selected regions of p15gag, including codon 3. In support of the above-described model, all of the viruses examined contained single nucleotide substitutions in codon 3. In addition, most of the replication-competent viruses that were sequenced appeared to result from simple mutation of Emv-3 rather than recombination with other endogenous murine leukemia viruses. These studies may provide a basis for development of a sensitive assay for the mutagenic activity of a variety of chemical carcinogens in vivo.